2022
DOI: 10.3390/s22010350
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Cost-Effective GNSS Sensors for Crustal Deformation Studies

Abstract: The geodetic monitoring of the continuous crustal deformation in a particular region has traditionally been the prerogative of the scientific communities capable of affording high-price geodetic-class instruments to track the tiny movements of tectonic plates without losing precision. However, GNSS technology has been continuously and rapidly growing, and in the last years, new cost-efficient instruments have entered the mass market, gaining the attention of the scientific community for potentially being high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Por otro lado, los receptores de bajo costo de una frecuencia resultan ser una buena opción para establecer una línea base, ya que se obtuvieron resultados similares a los expuestos por Zamora Maciel et al Por otro lado, respecto a lograr una alta precisión para trabajos de deformación de la corteza terrestre con receptores de bajo costo GNSS, los resultados alcanzados demuestran que no son óptimos para realizar el análisis de deformación de la corteza, ya que, se encuentra una menor precisión que la reportada por Tunini et al (2022). Esto se deriva del uso de modelos implementados en softwares científicos y antenas de nueva generación con calibración para mitigar el efecto multitrayectoria.…”
Section: Discussionunclassified
“…Por otro lado, los receptores de bajo costo de una frecuencia resultan ser una buena opción para establecer una línea base, ya que se obtuvieron resultados similares a los expuestos por Zamora Maciel et al Por otro lado, respecto a lograr una alta precisión para trabajos de deformación de la corteza terrestre con receptores de bajo costo GNSS, los resultados alcanzados demuestran que no son óptimos para realizar el análisis de deformación de la corteza, ya que, se encuentra una menor precisión que la reportada por Tunini et al (2022). Esto se deriva del uso de modelos implementados en softwares científicos y antenas de nueva generación con calibración para mitigar el efecto multitrayectoria.…”
Section: Discussionunclassified
“…Once the GPS, GLONASS, Galileo, and BeiDou systems are fully deployed, >140 satellites will be available for navigation and positioning applications (Li et al 2022). The number of GNSS signals and services already deployed has enabled new levels of performance in terms of accuracy, covering a wide range of application areas such as surveying and geomatics (Garrido et al 2018, 2019; Tunini et al 2022), engineering (Barzaghi et al 2018, Pipitone et al 2018, Xiao et al 2019), and environmental science (Awange 2018), and recent studies show the advantages of multi‐constellation solutions considering several GNSS positioning techniques (Gao et al 2019, Liu et al 2020, Dardanelli et al 2021, Li et al 2021, Paziewski et al 2021). With the current multi‐constellation scenario, a GNSS device previously able to receive satellite signals from about 8 GPS satellites under open sky can now access more than 30 satellites, albeit at the cost of reduced battery life.…”
Section: Figurementioning
confidence: 99%
“…Hamza et al [ 13 ] showed that on a basis of 30-min sessions the instruments can detect displacements from 10 mm upwards with a high level of reliability. In [ 14 ], Tunini et al matched, in parallel, the ZED-F9P receiver with two high-price geodetic instruments, all connected to the same geodetic antenna. They processed the data, together with the observations coming from a network of GNSS permanent stations operating in that region.…”
Section: Introductionmentioning
confidence: 99%